2020
DOI: 10.1371/journal.pone.0235926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight loss on the retinochoroidal structural alterations among patients with exogenous obesity

Abstract: ¶ Membership of the OCTA study group is provided in the acknowledgments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
3
20
1
2
Order By: Relevance
“…We did not include other demographic factors potentially associated with the CVI, as the smoking habitus 33 or the body mass index. 34 We mostly included patients with non-naïve DR undergoing multiple treatments, some of them with long-standing DME. The effect of some variables, such as age, type and duration of DM, or PPV, could have been missed or underestimated in our small group of naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…We did not include other demographic factors potentially associated with the CVI, as the smoking habitus 33 or the body mass index. 34 We mostly included patients with non-naïve DR undergoing multiple treatments, some of them with long-standing DME. The effect of some variables, such as age, type and duration of DM, or PPV, could have been missed or underestimated in our small group of naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in obese participants have shown that the subfoveal choroidal thickness is wider in patients with obesity compared to the healthy control subjects [ 16 , 17 ]. In another study displayed that there was no significant difference between underweight patients (BMI <18.50 mm/kg2) compared to the patients with normal weight (BMI: 18.50-24.99 mm/kg2) in the subfoveal choroidal thickness [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Normative databases for the subfoveal choroidal thickness have also been presented in the literature. The mean subfoveal choroidal thickness previously was reported 312.9 ± 65.3 mm, 265.5 ± 82.4 mm, and 348 ± 68 mm [ 18 - 20 ]. In our study, this thickness was found to be 340 ± 61.2 mm in the underweight group.…”
Section: Discussionmentioning
confidence: 99%
“…In einer prospektiven Studie wurden bei adipösen Patienten ( n = 60) eine signifikant verringerte FAZ ( p < 0,01) und ein signifikant höherer CDI im oberflächlichen Plexus ( p = 0,04) und im tiefen Plexus ( p = 0,01) gemessen. Es ergab sich kein Unterschied in den OCT-A-Parametern zwischen der Erstuntersuchung und dem 3‑Monats-Follow-up nach durchgeführter bariatrischer Chirurgie ( n = 30) trotz deutlicher Gewichtsreduzierung [ 1 ].…”
Section: Einfluss Von Risikofaktoren Für Kardiovaskuläre Erkrankungen Auf Die Oct-a-parameterunclassified
“…Andererseits weisen die Ergebnisse der bisherigen Studien darauf hin, dass Veränderungen der Mikrozirkulation auch vor Eintreten eines akuten kardiovaskulären Ereignisses nachweisbar sind, etwa bei Vorliegen von Risikofaktoren wie Diabetes mellitus [ 17 , 63 ] und Adipositas [ 1 , 32 ] und bei Erkrankungen wie asymptomatischem Vorhofflimmern [ 38 ] oder asymptomatischer Karotisstenose [ 37 ]. Bei einigen Erkrankungen sind die Veränderungen der OCT-A-Parameter auch dann nachweisbar, wenn fundoskopisch keine retinalen Gefäßveränderungen vorliegen [ 17 , 43 ], sodass die OCT‑A die Möglichkeit bietet, auch subklinische Veränderungen der Gefäßarchitektur nachzuweisen, was in Zukunft zu prognostischen Zwecken genutzt werden könnte.…”
Section: Zusammenfassungunclassified